Comparison of the three conventional methods for the postoperative atrial fibrillation prediction. Issue 6 (6th April 2017) - Aksu, Uğur; Gulcu, Oktay; Aksakal, Emrah; Topcu, Selim; Sevimli, Serdar; Tanboga, Ibrahim Halil
Abstract : Introduction: Although various risk factors have been defined for the development of postoperative atrial fibrillation (PAF), these parameters have not been adequately verified and validated. We investigated the atrial fibrillation detection capabilities of echocardiographic parameters in PAF developing and the determination of predictive values for clinical use. Method: We enrolled 60 consecutive patients with 234 lesions who underwent CABG surgery. All patients underwent preoperative echocardiographic evaluation. Patients were divided into two groups according to PAF development status. Results: The mean age of the patients was 67, and 73% were male and PAF occurred in 19 patients. In univariate analysis, left atrial volume index (LAVi), left ventricular global strain (LVGS) and ejection fraction were associated with PAF development. Parameters which were significant in univariate analysis were included in a logistic regression model to determine the independent predictors of PAF. LAVi was found to be an independent predictor of PAF. Conclusion: Although several parameters have been defined for PAF development, LAVi is more advantageous than the other conventional methods in clinical decision making.